Survei Keterampilan Dasar Sepak Bola di PS Pluto Luragung Tonggoh Kabupaten Kuningan - Permana, Syalwa Gilang; Wahyudi, Usman (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Based on the results of direct observations in the field with PS PLUTO Luragung Tonggoh players, Kuningan Regency, obtained about the level of basic soccer skills of PS PLUTO players. Most of the players are lacking in performing basic skills of passing, controlling and shooting the ball. The purpose of this study was to determine the level of basic skills of passing, control and shooting soccer at PS PLUTO Luragung Tonggoh Kuningan Regency. This study uses a quantitative descriptive method which aims to provide an overview of the level of basic soccer skills of PS PLUTO Luragung Tonggoh players in Kuningan Regency. This study uses a population of 30 players using census or total sampling as sampling. The results of this study that the level of basic soccer skills of passing and control has an average obtained by players of 20 with a percentage of 47% included in the moderate category. While the level of basic shooting skills has an average obtained by players of 15 with a percentage of 23% including in the moderate category. The conclusion of this study is that the level of basic soccer skills of passing and ball control and the level of basic shooting skills of PS PLUTO Luragung Tonggoh players in Kuningan Regency are included in the moderate category.